82 This is My Child: Piloting and Evaluating a Special Needs Screening Tool for Pediatric Emergency. (19th August 2020) - Craig, William; Kilmer, Christopher; Nicholas, David; Newton, Mandi; Zwaigenbaum, Lonnie
Abstract: Background: Parents of children with developmental disabilities (DD) including autism spectrum disorder (ASD) or behavioural conditions can be reluctant to inform the medical team of their child's diagnosis during a visit to the pediatric Emergency Department (PED). Knowing the child's sensitivities and needs, however, could make it easier for the healthcare team to provide the best possible care. A one-page tool, "This is My Child", was developed to bridge this gap. Objectives: Evaluate the ease of use, benefit to child's care, and overall acceptance of "This is My Child" from parental and health provider perspectives. Design/Methods: "This is My Child" was modified from an inpatient tool which helped communication between staff and children with ASD and their families. Developed with input from PED healthcare providers, the tool entailed ten questions pertinent to children who have communication and sensory processing challenges, as well as a prompt for additional comments. Families were recruited in the waiting room, and the study was open to all who were willing to participate. The completed tool was attached to the front of the ED chart prior to the child being seen. At the end of the ED visit, parents and treating healthcare providers completed a questionnaire evaluating the tool. Recruitment was deemed complete once 30 children with a prior diagnosis of a developmental/behavioural condition had been enrolled. Following analysis of the questionnaires, focus groups were held with participating ED healthcare providers. Results: Of 336 study participants recruited, 199 parents, 225 physicians and 135 nurses returned questionnaires. The large majority of parents, physicians and nurses indicated 'Strongly or Somewhat Agreed' that the tool was easy to understand. However, only 18% of physicians and 29% of nurses, yet 76% of parents, felt that the tool should be used for all children seen in the PED. This discrepancy between health care team and parental opinion was explored in the focus groups. Healthcare providers noted that the tool was beneficial in cases where unique developmental needs were reported. Concern was raised given the tool's perceived lack of relevance for children without special needs, as well as additional staff work for tool utilization. Conclusion: This easy to use form was welcomed by families, but less so by physicians. Work is ongoing to integrate these perspectives.